AI IMPLEMENTATION FRAMEWORK FOR TELECOMMUNICATION COMPANY DIGITAL TRANSFORMATION CASE STUDY: CALL CENTER SERVICE - Devi Lukitasari, Shinta
This thesis results an implementation framework of Artificial Intelligence (AI) in a telecommunication company which case study is Call Center service. The framework is intended to help the company to meet the requirements that must be owned and the actions that must be taken to gain the benefit from the utilization of AI. At present there are no standards available to guide company in implementing AI, policies or rules related to data for the development of AI solutions, or resources with specific expertise related to AI. Research questions that will be answered through this thesis are: how to implement AI capabilities in Call Center services in telecommunications companies, as well as how to measure the impact of implementing AI on business processes in Call Center services. Using Design Research Methodology, an implementation framework resulted is consisting of: Context, Components, Phase, and Role. The application of the implementation framework produces a speech to text model which its accuracy is 66.93% and a text classification model which its accuracy is 88.8%. The application of AI model in the Call Center service business process results in time efficiency up to 15% and increasing the effectiveness of problem analysis up to 35% compared to the previous business process.